Truth and politics toward a post-secular community. - DALLMAYR, FRED. ([S.l.] : STATE UNIV OF NEW YORK PR, 2022)
Endorses the pursuit of paradigm shifts in our understandings of faith, truth, and nature to remedy the "underside" of modernity and thus to inaugurate a post-modern (but not anti-modern) and post-secular (but not anti-secular) view of the world.
Intro -- Contents -- Preface -- Acknowledgments -- 1 Introduction: Emerging from Multiple Rifts -- 2 Post-Secularity and (Global) Politics: A Need for Redefinition -- Secularity versus Faith -- Religion and Ordinary Language -- Post-Secularity and Politics -- 3 Post-Secular Faith: Toward a Religion of Service -- Varieties of Religious Experience -- Toward a Religion of Service -- Multiple Faiths in a Shared World -- 4 Beyond Secular Modernity: Reflections on Taylor and Panikkar -- A Secular Age -- The Rhythm of Being -- Concluding Comments -- 5 "Man against the State": Self-Interest and Civil Resistance -- Herbert Spencer and Social Darwinism -- Civil Disobedience and Dissent -- Dissent in Community -- 6 Neo-Liberalism and Its Critics: Voices from East and West -- Minimal or Neo-Liberal Democracy -- Beyond Minimalism: Voices from South Asia -- Beyond Minimalism: Voices from East Asia -- Concluding Remarks -- 7 Individualized Life: The Plight of Narcissism -- Individualized Society -- Regimes of Narcissism, Regimes of Despair -- Pandemic, World Alienation, and Vita Activa -- 8 Holism and Particularism: Panikkar on Human Rights -- Is "Human Rights" a Western Concept? -- Rights and Right(ness) -- 9 Falling Upward Communally: A Tribute to Richard Rohr -- The Universal Christ -- The Divine Dance -- Falling Upward -- Concluding Remarks -- Notes -- Index.
JSTOR
Keywords: Political science -- Philosophy; Postsecularism; Individualism; Postsécularisation.